Using customer journey mapping to improve public services: A critical analysis of the literature = Wykorzystanie mapowania podróży klienta do usprawniania usług publicznych: krytyczna analiza literatury - Ludwiczak, Anna (Zielona Góra: Faculty of Economics and Management Press)
Providing clients with public services that will meet their needs and expectations requires not only testing their satisfaction. In order to better improve service processes in the context of customer orientation, customer experiences should be identified and taken into account in the process of continuous improvement. A tool that can be used for this purpose is Customer Journey Mapping (CJM).
Keywords: customer journey map; customer experience; continuous improvement; public services; public administration; mapowanie ścieżki klienta; doświadczenia klientów; ciągłe doskonalenie; usługi publiczne; administracja publiczna